Integration of the several MCDM results according to methods importance - Vinogradova, Irina (Lietuvos matematikos rinkinys, 2016)
Multiple criteria decision making methods (MCDM) are widely used in different areas. In theory the best or the most suitable method isnt defined, so in order to ensure the correct decision, often several MCDM are used. In the case MCDM results of the methods are different, the solution is ambiguous. In this publication, to make decision based on several MCDM, it is proposed to combine all used methods results in a single value, according to importance of the methods in the solvabletask. The method, which is more stable to small changes of the data, has a higher importance (weight) for integrated result. The results of different methods are not comparable with each other, for this reason it is necessary to normalize the obtained data, to unify their scale.
Keywords: MCDM; integration of results; importance; weights; stability